Bycatch in trawl-fisheries. Sub-project 3 - Sundet, Jan Henry; Hauan, Marit Anne (Nofima AS, 2000)
Published by Nofima AS (former Fiskeriforskning). ISBN 82-7251-440-0. The main goals of this sub-project were to evaluate whether interviewing fishers could be an appropriate method to reveal quantities of the bycatches in the Norwegian trawl fisheries, and to describe the knowledge about and the fishermen's attitudes to the bycatch problem. In total 11 crew members on trawlers from a fishing company in Lofoten were interviewed. The data from the interviews showed that the trawl fishermen had very little focus on bycatch as we defined it, and the interviews gave only partly information on reliable quantities of the different species. Interviews are a good method revealing the fisher’s knowledge, norms and attitudes, but should be accompanied by practical recordings when it comes to quantitative estimates. No differences in the attitudes to bycatch were found between officers and fishers among the informants. But there seem to be a difference both in knowledge of species and the attitude to exploitation of bycatch, between fishers with experience from the coastal fishery and those with a strict trawl fishery career. The shipping companies are much more crucial in defining the premises for a future exploitation of the bycatch in the trawl fishery than the fishermen onboard the trawlers.